Clinical and Dopamine Transporter Imaging Characteristics of Leucine Rich Repeat Kinase 2 (LRRK2) and Glucosylceramidase Beta (GBA) Parkinson's Disease Participants in the Parkinson's Progression Markers Initiative: A Cross‐Sectional Study. Issue 5 (19th February 2020) - Simuni, Tanya; Brumm, Michael C.; Uribe, Liz; Caspell‐Garcia, Chelsea; Coffey, Christopher S.; Siderowf, Andrew; Alcalay, Roy N.; Trojanowski, John Q.; Shaw, Leslie M.; Seibyl, John; Singleton, Andrew; Toga, Arthur W.; et al.
Abstract: Background: There are limited data on the phenotypic and dopamine transporter (DAT) imaging characterization of the Parkinson's disease (PD) patients with leucine rich kinase 2 ( LRRK2 ) and glucosylceramidase beta ( GBA ) mutations. Objective: The objective of this study was to examine baseline clinical and DAT imaging characteristics in GBA and LRRK2 mutation carriers with early PD compared with sporadic PD. Methods: The Parkinson's Progression Markers Initiative is an ongoing observational longitudinal study that enrolled participants with sporadic PD, LRRK2 and GBA PD carriers from 33 sites worldwide. All participants are assessed annually with a battery of motor and nonmotor scales, 123‐I Ioflupane DAT imaging, and biologic variables. Results: We assessed 158 LRRK2 (89% G2019S), 80 GBA (89 %N370S), and 361 sporadic PD participants with the mean (standard deviation) disease duration of 2.9 (1.9), 3.1 (2.0), and 2.6 (0.6) years, respectively. When compared with sporadic PD, the GBA PD patients had no difference in any motor, cognitive, or autonomic features. The LRRK2 PD patients had less motor disability and lower rapid eye movement behavior disorder questionnaire scores, but no meaningful difference in cognitive or autonomic features. Both genetic cohorts had a higher score on the impulse control disorders scale when compared with sporadic PD, but no difference in other psychiatric features. Both genetic PD cohorts had less loss of dopamine transporter on DAT imaging when compared with sporadic PD. Conclusions: We confirm previous reports of milder phenotype associated with LRRK2 ‐PD. A previously reported more aggressive phenotype in GBA ‐PD is not evident early in the disease in N370s carriers. This observation identifies a window for potential disease‐modifying interventions. Longitudinal data will be essential to define the slope of progression for both genetic cohorts. Trial Registration: ClinicalTrials.gov (NCT01141023). © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.